A low-cost traffic generation system using open-source software for accessible cyber ranges - Mahmod Attar Bashi, Zainab Senan; Saniza, Auni Fatini; Shafudin, Nazihah; Sakka, Oula; Basri, Atikah Balqis; Mohd Aman, Azana Hafizah (PENERBIT UniMAP, 2026)
This project implements a comprehensive open-source traffic generator designed for cyber ranges and network defence labs. The project addresses the growing demand for advanced cybersecurity training tools that can simulate real-world network traffic and attack scenarios. By providing a hands-on laboratory environment, the tool directly enhances cybersecurity education by allowing students to interact with and analyse dynamic network conditions and malicious traffic patterns. Traditional traffic generators often lack the flexibility and usability required for educational and research applications, creating a gap that this project seeks to fill. The developed traffic generator features an intuitive configuration and control interface, a robust traffic generation engine capable of simulating diverse network traffic patterns, and support for various protocols, including TCP, UDP, ICMP, and HTTP. Prepackaged attack scenarios, such as DDoS, ransomware, and reconnaissance, enhance realistic cybersecurity training. The tool prioritizes customization options and comprehensive reporting to maximize its functionality and adaptability to different use cases. By offering an effective and accessible solution, this project significantly enhances the training and preparedness of cybersecurity professionals, contributing to the development of secure and resilient network infrastructures.